2014
DOI: 10.1159/000365080
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in Melasma in Korean Women

Abstract: Background: There has been a paucity of data about the difference in gene expression between melasma lesional skin and normal adjacent one. Objective: Our aim was to identify novel genes involved in the pathogenesis of melasma. Methods: We performed a microarray analysis and confirmed the results on quantitative real-time polymerase chain reaction (qRT-PCR) in Korean women with melasma. Results: There were 334 genes whose degree of expression showed a significant difference between melasma lesional skin and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…Consistent with our previous microarray data (Chung et al., ), quantitative reverse transcription PCR (qRT‐PCR) confirmed that adiponectin mRNA and protein level were lower in the lesional skin of melasma patients compared with non‐lesional skin (Figure a). Interestingly, while the expression of cytokeratin and melan‐A appears to be comparable, by IF staining, we observed decreased AdipoR1 and AdipoR2 expression in the basal layer of lesional skin compared with non‐lesional skin of melasma patients (Figures b, Fig ).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our previous microarray data (Chung et al., ), quantitative reverse transcription PCR (qRT‐PCR) confirmed that adiponectin mRNA and protein level were lower in the lesional skin of melasma patients compared with non‐lesional skin (Figure a). Interestingly, while the expression of cytokeratin and melan‐A appears to be comparable, by IF staining, we observed decreased AdipoR1 and AdipoR2 expression in the basal layer of lesional skin compared with non‐lesional skin of melasma patients (Figures b, Fig ).…”
supporting
confidence: 90%
“…Interestingly, our previous work has shown that using cDNA analysis of melasma skin biopsy specimens from five Korean women, adiponectin mRNA expression was significantly decreased in the lesional skin in comparison with the non‐lesional skin (Chung et al., ). Hence, in this study, we pursue the role of adiponectin and another well‐known AMPK activator, AICAR on melanogenesis and speculate clinical relevance of adiponectin in melasma, a common but refractory hyperpigmentary skin disorder.…”
mentioning
confidence: 99%
“…In our previous study using DNA microarray from melasma lesions, GDA was shown to be one of the most upregulated genes, which was validated by qRT-PCR analysis [17]. KCs were the most abundant type of cells obtained from a skin biopsy using a 2 mm punch, and high GDA expression in cultured KCs suggested that KCs are the source of GDA in hyperpigmented lesions.…”
Section: Discussionmentioning
confidence: 67%
“…Similar to melasma, Riehl's melanosis (RM) is characterized by diffuse hyperpigmentary patches on the face and neck and is aggravated by UV irradiation and/or inflammation [15,16]. In our previous study, we found that guanine deaminase (GDA) mRNA expression was 5 to 14-fold higher in melasma lesion tissue than in non-lesion tissue [17]. In purine metabolism, guanine is converted into xanthine by GDA, a ubiquitous aminohydrolase enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies indicate that several proteins and cellular components, including α-melanocyte-stimulating hormone, stem cell factors, ckit, vascular endothelial growth factor, and nerve growth factor, are involved in the pathogenesis of melasma. 7 Topical agents such as hydroquinone and superficial chemical peels are the current standard for melasma treatment, but concern about side effects and long-term safety has spurred efforts to develop alternative treatment options. 8 Oral intake or intralesional injection of ascorbic acid or tranexamic acid has been clinically tried.…”
Section: Introductionmentioning
confidence: 99%